Development of a risk stratification model for pharmaceutical care in HIV patients - Ramón Morillo-Verdugo; José Manuel Martínez-Sesmero; Alicia Lázaro-López; Javier Sánchez-Rubio; Herminia Navarro-Aznárez; Monike deMiguel-Cascón (Farmacia Hospitalaria)
Background: The increasing number of HIV-patients and their complexity makes it necessary to develop risk classification tools to improve the optimization of resources. Objective: To design a risk-stratified model for pharmaceutical care (PC) in HIV-patients. Methods: A cross-sectional, multicenter study. An expert panel was created by Hospital Pharmacist experienced in PC for HIV-patients. The study was designed in 4 phases. The first phase included a review of literature and the development of a summary of the scientific evidence available. According to their score, patients were stratified into three levels of PC. In the second and third phases, a sample of patients was assessed and data information was recorded. The overall analysis also allowed pharmacists to define the actions to be applied at each level of priority. Finally, each stratification model was applied to a new sample of patients to verify their applicability and usefulness. Results: All variables included in the model were weighted in terms of their relative relevance compared to the rest. A sample of 215 patients was evaluated to obtain their score and distribution: Priority-1: score ≥ 32 and 10% of the sample; Priority-2: 18-31.9 and 30%; Priority-3: ≤ 17 and 60%. The PC interventions corresponding to each level of priority were classified into “pharmacotherapeutic monitoring”, “training, education and patient tracking” and “coordination of all the healthcare team members”. Conclusions: This study supported the design and adaptation of a selection and stratification model for PC in HIV-patients as a tool to identify those who may benefit from priority intervention.